2019
DOI: 10.1186/s43008-019-0001-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification, prevalence and pathogenicity of Colletotrichum species causing anthracnose of Capsicum annuum in Asia

Abstract: Anthracnose of chili (Capsicum spp.) causes major production losses throughout Asia where chili plants are grown. A total of 260 Colletotrichum isolates, associated with necrotic lesions of chili leaves and fruit were collected from chili producing areas of Indonesia, Malaysia, Sri Lanka, Thailand and Taiwan. Colletotrichum truncatum was the most commonly isolated species from infected chili fruit and was readily identified by its falcate spores and abundant setae in the necrotic lesions. The other isolates co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 53 publications
6
78
0
11
Order By: Relevance
“…The gloeosporioides complex currently comprises 49 accepted species based on phylogenetic analyses and morphological approaches, with pathogenic and endophytic species known in a variety of hosts (Jayawardena et al ., 2016; Guarnaccia et al ., 2017; Sharma et al ., 2017; Vieira et al ., 2017; De Silva et al ., 2019). Although it has been argued that C .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gloeosporioides complex currently comprises 49 accepted species based on phylogenetic analyses and morphological approaches, with pathogenic and endophytic species known in a variety of hosts (Jayawardena et al ., 2016; Guarnaccia et al ., 2017; Sharma et al ., 2017; Vieira et al ., 2017; De Silva et al ., 2019). Although it has been argued that C .…”
Section: Discussionmentioning
confidence: 99%
“…The acutatum complex comprises 38 accepted species, all isolated from anthracnose‐affected crops worldwide (Jayawardena et al ., 2016; De Silva et al ., 2019; Damm et al ., 2020). C .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a physical barrier, the cuticle surrounds the epidermis of fruits and serves a number of functions including (a) to protect the plant against the physical, environmental and biological stresses and pathogen invasion, (b) to reduce the effects of internal water loss, and (c) to maintain plant organ integrity by providing mechanical support (Belge et al, ; Chen et al, ; Lara, Belge, & Goulao, ). In pathogenicity tests, C. truncatum isolates are pathogenic on Capsicum fruits after wounding the fruit surface, and most produced a low level of infection on nonwounded fruit (De Silva et al, ; Ramdial & Rampersad, ). The life cycle of C. truncatum in Capsicum sp.…”
Section: Introductionmentioning
confidence: 99%
“…C. capsici ‐ Damm, Woudenberg, Cannon, & Crous, ; Ramdial & Rampersad, ) and more recently by C. brevisporum , albeit with lower incidence compared to C. truncatum (Villafana, Ramdass, & Rampersad, ). C. truncatum was the predominant species of Colletotrichum associated with anthracnose of chili in Asia and is widely distributed throughout Asia, Australia, and South America (De Silva, Ades, Crous, & Taylor, ; De Silva et al, ; Diao et al, ; Mongkolporn & Taylor, ; Sharma, Kumar Pinnaka, & Shenoy, ). Multilocus phylogeny revealed that the recently characterized Colletotrichum magnum species complex consists of nine closely‐related species which includes C. brevisporum (Damm et al, 2019).…”
Section: Introductionmentioning
confidence: 99%